Pengaruh Dana Syirkah Temporer dan Usia Dewan Direksi terhadap Profitabilitas Bank Syariah Indonesia, Bank Muamalah Indonesia, Bank Mega Syariah dan Bank BCA Syariah Periode 2021-2023 (Jurnal Ekonomi Syariah dan Pariwisata Halal, 2025)
Profitability is the final result and goal of a company's establishment. A company that has a high profitability value means that the company is successful in running its business operations. Many factors affect profitability, from Corporate Governance factors to Financial Factors. This research method is quantitative descriptive with the object of research being 4 large Islamic banks in Indonesia. The data analysis technique is panel data regression using eviews. The tests used are model selection tests, classical assumption tests and hypothesis tests. The results of this study are the coefficient value and negative t statistic and the probability value of 0.0045
Keywords: Islamic Bank; Temporary Syirkah Fund; Age of Board of Directors; Profitability